The efficiency of defense-augmented production function for G20 countries: An analysis of the relationship with Country Fragile Index - Al-qalawi, Usama; AlQudah, Anas; Alwaked, Ahmad A.; Al-Rabbaie, Arqam Abdul Razzaq (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the efficiency of defense-augmented production in G20 countries and its relationship with the Fragile Index, assessing the impact of defense spending on production efficiency. This study utilizes Stochastic Frontier Analysis (SFA) and panel autoregressive distributed lag (ARDL) models, analyzing a panel dataset covering 2006 to 2021. Key variables include GDP, labor, capital, defense spending, and the Fragile Index for G20 countries. The study demonstrates a positive correlation between production inefficiency and country fragility. Countries with higher levels of fragility exhibit lower production efficiency. Additionally, while capital and labor inputs enhance production efficiency, defense spending is linked to inefficiencies. The findings emphasize the need for policymakers and defense sector stakeholders in G20 nations to address fragility-related factors in order to enhance overall production efficiency in defense-related industries. This study offers new insights into the relationship between defense spending, production efficiency, and national fragility. It adds to the literature on defense economics and production efficiency, providing a comprehensive framework for assessing the impact of fragility on economic performance in G20 countries.